(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2020)
Through the analysis of published and unpublished archival sources, this paper is aimed at retracing the first three steps in the history of Dino Campana’s Canti Orfici, by presenting all the issues related to its textual systematization. The history begins with the 1914 princeps edition, which though far from being flawless, is the only one licensed by the author. In the second edition, published by Vallecchi in 1928 and prefaced by Bino Binazzi, peritexts are eliminated and an appendix of poems previously only published in journals is introduced. It will be up to Enrico Falqui – at the invitation of the publisher Enrico Vallecchi – to bring the text back to its original lectio in 1941, solving ecdotic issues with the help of Giuseppe De Robertis and Gianfranco Contini. Falqui also edits a volume of Campanian unpublished poems, found by the poet’s brother, Manlio, with whom the critic had been in contact since 1938.